The Role of Higher Education in Building Religious Tolerance: A Study on the Implementation of Moderation Attitudes among Aceh’s State Islamic Religious Higher Education Institution Students - Syibran Mulasi; Fedry Saputra (STAI Hubbulwathan Duri, 2024)
Fostering an attitude of religious moderation among students can be achievable when all stakeholders collaborate to create a cohesive understanding of moderation. This study examines the role of universities in promoting religious moderation among students at State Islamic Religious Higher Education Institution (hereafter, PTKIN) Aceh. Utilizing a qualitative approach, data were collected through interviews, focus group discussions (FGDs), and observations. Interviews involved academics focused on religious moderation at PTKIN, while FGDs included students from five state Islamic universities in Aceh, selected purposively to provide insights on students' attitudes and views on religious moderation. Observations were conducted to assess students' attitudes and behaviors. The findings reveal that students exhibit moderate attitudes in daily life, are willing to collaborate socially and respect others' rights and obligations in worship. Challenges in instilling religious moderation values include the need for acceptance of the term within the context of local wisdom and avoiding the perception of moderation as a new religious project. Solutions involve preparing a curriculum based on Islamic tolerance and strengthening the role of religious moderation houses to promote Islamic washatiyah values among students, facilitating easier understanding and implementation in daily life.